2007
DOI: 10.4049/jimmunol.179.6.3570
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Neutrophils Require JNK2 MAPK forToxoplasma gondii-Induced IL-12p40 and CCL2/MCP-1 Release

Abstract: The MAPK family member JNK/stress-activated MAPK (SAPK) is involved in extracellular stress and proinflammatory cytokine responses, including production of cytokines such as IL-12. The JNK1 and 2 isoforms are widely expressed, but JNK3 is largely restricted to tissues of the brain, testis, and heart. In this study, we focus on mouse neutrophils, a cell type in which JNK/SAPK expression and activity has been given little study. We used Western blot analysis to examine expression patterns of JNK/SAPK in wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 60 publications
1
33
0
Order By: Relevance
“…S2). These data suggested that JNK1 in neutrophils is not critical for developing arthritis and are consistent with other reports that mature neutrophils have little, if any, expression of JNK1 (29).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…S2). These data suggested that JNK1 in neutrophils is not critical for developing arthritis and are consistent with other reports that mature neutrophils have little, if any, expression of JNK1 (29).…”
Section: Resultssupporting
confidence: 92%
“…In addition, the repletion of WT neutrophils did not recapitulate arthritis in JNK1-deficient mice. Although FcγR expression by neutrophils contributes to the generation of arthritis (28), the paucity of JNK1 reported in mature neutrophils (29) suggested that these cells use signaling pathways that are not entirely similar to MCs. Other cell types might also be involved in the attenuated course of arthritis in JNK1-deficient mice, including macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In neutrophils, IL-12 and CCL2/monocyte chemoattractant protein 1 (MCP-1) production require JNK2, as polymorphonuclear leukocytes (PMN) from JNK2 Ϫ/Ϫ mice were totally deficient in the production of these cytokines (56). Neutrophil chemotaxis is also partially dependent on JNK2 (56). Using pharmacological inhibitors, we found that B7-2 upregulation in T. gondiiinfected cells is dependent on JNK signaling.…”
Section: Discussionmentioning
confidence: 87%
“…In macrophages, autophosphorylation of p38 is the dominant player in activating IL-12 secretion (27). In neutrophils, IL-12 and CCL2/monocyte chemoattractant protein 1 (MCP-1) production require JNK2, as polymorphonuclear leukocytes (PMN) from JNK2 Ϫ/Ϫ mice were totally deficient in the production of these cytokines (56). Neutrophil chemotaxis is also partially dependent on JNK2 (56).…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, pharmacologic inhibition of JNK almost completely prevented LPS-mediated production of NOS2/NO and TNF-a, indicating the critical importance of JNK in these immune responses. Although JNK1 and JNK2 may have largely overlapping and redundant functions, studies using transgenic approaches or genetic deficiency of specific JNK isoforms indicate that it is primarily JNK2 that is responsible for these innate responses (56)(57)(58). In this regard, our discovery of JNK2 as the primary target for direct alkylation implicates JNK2 as a direct site for inhibition of JNK signaling and innate immune responses by acrolein.…”
Section: Discussionmentioning
confidence: 99%